Foliar fertilization of sodium selenite and its effects on yield and nutraceutical quality in grapevine - Sariñana-Navarrete, María de los Ángeles; Hernández-Montiel, Luis Guillermo; Sánchez-Chávez, Esteban; Reyes Pérez, Juan José; Murillo-Amador, Bernardo; Preciado-Rangel, Pablo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Selenium (Se) is an essential micronutrient for humans, but in plants, this essentiality has not been demonstrated. However, the supplementation of Se in crops has been shown to improve the yield and the quality of the edible part. The objective of this research was to evaluate the effect of Se foliar fertilization on yield, nutraceutical quality and Se accumulation in grape. Five doses of Se (Na2SeO3 at 0.25, 0.5, 0.75, 1.0 and 1.25 mg.L-1) and a control were evaluated. The results obtained showed that the application in low doses of Se increased the yield; high doses increase nutraceutical quality and induced the accumulation of Se in grapes. In conclusion, the grapevine is a crop with the potential to be biofortified and improve the quality of grape.